Management of odontogenic giant radicular cyst with maxillary sinus expansion: Penatalaksanaan odontogenic giant radicular cyst dengan perluasan sinus maksilaris - Rachmady Nofriansyah; A. Arfandi Arifuddin (Makassar Dental Journal PDGI Makassar, 2024)
Giant radicular cyst is an odontogenic cyst that is often found in the oral cavity. This paper describes the management of GRC with maxillary sinus expansion. A 13-year-old boy came to Labuang Baji Hospital Makassar with a complaint of a lump on the right maxilla experienced for about 1 year. History of trauma while playing football. Physical examination, lump size about 4x2x1.5 cm in the vestibulum labialis anterior RA area; no tenderness, spongy consistency, the same color as the surrounding tissue, there is crepitation and yellowish clear liquid punching test. CT-scan supporting examination showed a unilocular picture with expan-sion to the maxillary sinus area with bone destruction. It was concluded that the management of GRC with expansion of the maxil-lary sinus can be done by enucleation by taking into account the anatomy of the maxillary sinus so as to provide healing.